Automatic Single-Cell Transfer Module - Uvet, Huseyin; Hasegawa, Akiyuki; Ohara, Kenichi; Takubo, Tomohito; Mae, Yasushi; Arai, Tatsuo (CRC PRESS-TAYLOR & FRANCIS GROUP, 2012)
Conventional hybrid microfluidic systems have many functions such as separation, sorting, and filtering of biological particles. These hybrid systems are required for delivering particles into microfluidic chips and for their dexterous on-chip manipulation. Successful realization of these functionalities requires visual sensing of particles. However, only a limited number of studies are available on on-chip visual sensing techniques as well as on retrieval of living cells into microfluidic devices and their manipulation thereafter. Automated continuous individual cell transfer is a critical step in single-cell applications using microfluidic devices. Cells must be aspirated gently from a buffer before transferring to an operation zone to avoid artificially perturbing their biostructures. Vision-based manipulation is a key sensing technique that allows nondestructive cell detection. In this chapter, we present a design for an automated single-cell transfer module that can be integrated with complex microfluidic applications that examine or process one cell at a time such as the current nuclear transplantation method. The aim of the system is to automatically transfer mammalian fibroblasts (similar to 15 mu m) or oocytes (similar to 100 mu m) one by one from a container to a polydimethylsiloxane (PDMS) microchannel and then transport them to other modules. The system consists of two main parts: a single-cell suction module and a disposable PDMS-based microfluidic chip controlled by external pumps. The desired number of vacuumed cells can be directed into the microfluidic chip and stored in a docking area. From the batch, they can be moved to the next module by activating pneumatic pressure valves located on two sides of the chip. The entire mechanism is combined with monitoring systems that perform the detection/tracking and control program.
Keywords: SYSTEMS; TOOLS; Computer Science; Engineering; Robotics